Electroanalysis of Carbendazim using MWCNT/Ca‐ZnO Modified Electrode - Malode, Shweta J.; Keerthi, Prabhu K.; Shetti, Nagaraj P.; Kulkarni, Raviraj M. (Electroanalysis (New York, N.Y.), 2020)
The present research involves the report on electrochemical deportment of Carbendazim (MBC) at multiwalled carbon nanotubes and calcium‐doped zinc oxide nanoparticles altered nanocomposite based carbon paste electrode (MWCNTs/Ca‐ZnO‐CPE). The modified carbon paste evidenced manifest electrocatalytic behavior for MBC in 0.2 M phosphate buffer (PB) solutions. Cyclic voltammetry (CV), linear sweep voltammetry (LSV), and square wave voltammetry (SWV) techniques were used for the analysis. The working electrode assembly exhibits faster electron transfer of MBC with increase in the peak current. At bare CPE, MBC showed maximum peak current of 1.098 μA at potential 0.7568 V whereas at MWCNT/Ca‐ZnO/CPE peak current of 5.203 μA was observed at potential 0.7541 V in 0.2 M PBS of pH 7.0 at the sweep rate of 50 mV s−1. The synthesized 5 % Ca‐ZnO nanoparticles (NPs) were characterized by X‐ray diffraction (XRD), Scanning electron microscopy (SEM), Energy dispersive X‐ray analysis (EDX), and Transmission electron microscopy (TEM) analysis. Various factors influencing the voltammetry of MBC such as pre‐concentration time, pH, sweep rate, and amount of MBC were studied and from the studies we observed that the response was found to be diffusion‐controlled. The concentration variation studies for MBC was watched in the linear working range of 0.01 μM to 0.45 μM and the detection limit was found by SWV technique.